Social anxiety - Johnson, Laura (Laura L. C.) (--For dummies., 2025)
"Feeling anxious around people? Not sure where to start? Then this user-friendly, practical resource might be exactly what you're looking for. This workbook helps you tackle your fear of judgment and worry about what others think of you. You'll find simple step-by-step instructions, worksheets and real-world examples to help you gain insight and control over your social anxiety. Social Anxiety For Dummies is a solution-focused guide to creating a new mindset about social anxiety and your ability to cope with it. This book has easy-to-understand information and effective strategies to help you make positive changes in your life. Packed with tips and tools to conquer your social anxiety Create positive self-talk, reduce avoidance and face your fears Discover how to deal with social situations, dating, public speaking, kids with social anxiety and workplace anxiety Explore how positive psychology can help you live a life of meaning, with or without social anxiety A complete guide with proven ideas, this is a jargon-free and a fun approach to gaining mastery over your social anxiety. Social Anxiety For Dummies puts you on the fast track to building your self-esteem and confidence." --